A Hybrid Method for Predicting the Bistatic Target Strength Based on the Monostatic Scattering Sound Pressure Data - TANG, Yuhang; FAN, Chenyu; LI, Yinhao; CHEN, Changxiong; PENG, Zilong (Archives of Acoustics, 2025)
To predict the scattered acoustic field for underwater targets with separate transmission and reception points, a forecasting method based on limited scattered acoustic pressure data is proposed. This method represents the scattered acoustic field as the product of n acoustic scattering transfer function and a source density function. By performing numerical integration, the transfer function is obtained using the model surface grid information as input. An equation system concerning the unknown source density function is then derived using the computed scattering transfer matrix, the principle of acoustic reciprocity, and the geometric properties of the target. The unknown source density function is solved using the least squares method. The scattered field with separate transmission and reception points is then obtained by multiplying the calculated transfer matrix with the estimated source density function. This paper applies the finite element method (FEM) to solve the scattering field for a benchmark model with separate transmission and reception points. Using a subset of the elements as input, predictions of the omnidirectional scattered field were made. The predicted results were subsequently compared with those obtained from FEM simulations. The simulation results demonstrate that the proposed method maintains high computational accuracy and is applicable to the prediction of low-frequency scattered fields from underwater targets with spatially separated source and receiver. Further comparison with the FEM-calculated target strength patterns across varying incident–reception angles reveals a high level of agreement, indicating that accurate bistatic target strength predictions can be achieved with a limited amount of input data.